2017
DOI: 10.5267/j.esm.2017.3.002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mechanical properties of jute fiber strengthened epoxy/polyester composites

Abstract: In recent years, efforts have been made to produce advanced composite materials in order to lessen environmental impact and to extent sustainability. Traditional materials are largely substituted by composites due to their greater properties like flexural strength, low thermal expansion and high strength. Numerous studies are present that show the process of composite materials reinforcement with natural fiber to improve mechanical and thermal properties. The vital aspect of exploitation of natural fiber in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…On the other hand, natural and synthetic fibres (e.g., jute fibre and polyaramid FORTA fibre) with different sizes and volumes or weight percentages are among the previously used materials for mixing in the composition of asphalt mixture as reinforcing material. [53][54][55][56][57][58][59][60] For manufacturing the HMA mixture of this research, LDPE additive (in the granule shape shown in Figure 7) was used as binder modifier, and the fracture toughness results of such modified HMA mixture were compared with the control and unmodified HMA mixture to examine the effect of this modifier on lowtemperature cracking response of asphalt materials. For…”
Section: Materials and Fracture Toughness Testingmentioning
confidence: 99%
“…On the other hand, natural and synthetic fibres (e.g., jute fibre and polyaramid FORTA fibre) with different sizes and volumes or weight percentages are among the previously used materials for mixing in the composition of asphalt mixture as reinforcing material. [53][54][55][56][57][58][59][60] For manufacturing the HMA mixture of this research, LDPE additive (in the granule shape shown in Figure 7) was used as binder modifier, and the fracture toughness results of such modified HMA mixture were compared with the control and unmodified HMA mixture to examine the effect of this modifier on lowtemperature cracking response of asphalt materials. For…”
Section: Materials and Fracture Toughness Testingmentioning
confidence: 99%
“…In one of the studies, Kaushik et al. [18] surveyed the mechanical properties of jute reinforced epoxy and polyester composites. They used jute fibre at five different amounts (11%, 22%, 33%, 44% and 55%) and at each composition polyester-based composites reached better impact strength values as compared to epoxy-based composites [18].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 shows important factors and their levels. In the present study, two-factor and five-level historical data model was chosen for establishing the relationship between the response (tensile strength) and the variables (fibre length and fibre weight ratio) (Velumani et al, 2013;Ihueze1 et al, 2012;Kaushika et al, 2017). Design Expert version 10, DX10-05-3 software is used for this purpose.…”
Section: Development Of Historical Data Rsm Modelmentioning
confidence: 99%